2013
DOI: 10.1093/ntr/ntt108
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Craving During Smoking Cessation: An Ecological Momentary Assessment Study

Abstract: Attentional bias can be assessed in the natural environment using EMA during smoking cessation, and attentional bias is a correlate of craving during the early stages of a quit attempt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 36 publications
(37 reference statements)
4
35
1
Order By: Relevance
“…These findings are similar therefore to two other studies, which also reported crosssectional associations between attentional processes and craving in smokers trying to stop smoking (Waters et al, 2014) and heroin-addicts in treatment (Marhe et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…These findings are similar therefore to two other studies, which also reported crosssectional associations between attentional processes and craving in smokers trying to stop smoking (Waters et al, 2014) and heroin-addicts in treatment (Marhe et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Data from the other assessments will be reported elsewhere. At the quit day session some participants volunteered to participate in an ecological momentary assessment study which involved carrying a personal digital assistant (PDA) for 1 week in the field after the quit day (see Waters et al 27 for EMA protocol). On the PDA, self-report and reaction time data were collected including the SS task.…”
Section: Methodsmentioning
confidence: 99%
“…The SS task assessed attentional bias to smoking cues as described in Waters et al 27 As noted above, the task was administered on a PDA (HP iPAQ Pocket PC) in the field for 1 week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Waters et al [20] showed that attentional bias toward smoking cues was related to higher craving on the between-subjects level; however, this effect was not found on the within-subjects level: Instances where an individual's attentional bias was higher than the individual's average bias score were not related to higherthan-average cravings for the individual. This contradicts theoretical models which assume that higher attentional bias goes along with higher cravings.…”
Section: Within-individual Changementioning
confidence: 99%